COMFORT THEORY-BASED NURSING INTERVENTIONS TO ENHANCE POSTOPERATIVE COMFORT IN ELDERLY PATIENTS - Aldilla Dwi Estri Hastuti; Satriya Pranata (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
Elderly postoperative patients experience multidimensional discomfort affecting physical, psychological, social, and spiritual wellbeing. Kolcaba's Comfort Theory provides a holistic framework for addressing these needs. To identify comfort theory-based nursing interventions for elderly postoperative patients and analyze their effectiveness. Methods: Systematic literature review of articles from PubMed, ScienceDirect, ProQuest, and Google Scholar (2020-2025) using narrative synthesis. Ten studies demonstrated that comfort-based interventions including pain management, emotional support, non-pharmacological techniques, and environmental modifications significantly improved patient outcomes. Physical and psycho-spiritual dimensions were most influential, reducing pain, anxiety, and postoperative complications while enhancing sleep quality and satisfaction. Social and environmental dimensions provided crucial reinforcement. Nurse competency and family involvement supported implementation, while workload and limited resources posed challenges. Comfort theory-based interventions effectively enhance elderly postoperative recovery through holistic, multidimensional approaches. Integration into evidence-based practice is essential for optimal patient outcomes.